Simultaneous over- and underconfidence: Evidence from experimental asset markets - Boris Maciejovsky; Erich Kirchler (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2001)
In this paper individual overconfidence within the context of an experimental asset market is investigated. Overall, 72 participants traded one risky asset on six markets of 12 participants each. The results indicate that individuals were not generally overconfident. Moreover, overconfidence was found to be moderated by the methodology used. Participants were well-calibrated as well as over- and underconfident during some trading periods with respect to the accuracy of their predictions, while their subjective confidence intervals were generally too narrow and overconfidence was found to increase with experience.
urn:nbn:de:kobv:11-10049901
Keywords: C90; D40; 330; Experimental Economics; Financial Markets; Overconfidence